Patients' beliefs about the causes of myomas: a pilot study from a large European city - Matthias David; Miriam Alpheus; Heribert Kentenich (Taylor & Francis Group, 2017)
Introduction: Patients usually develop subjective concepts about their illness, which then influences their further health behaviors and treatment decisions. This study aimed to evaluate several possible patient beliefs about the causal factors of illness, in a large sample of women seeking treatment for myomas. Methods: From November 2011 to October 2013, all patients at a specialized myoma clinic in a large European city were surveyed about their beliefs about the causes of myomas. We used a modified version of the Patient Theory Questionnaire from Zenz et al., which presented 16 of the most common possible beliefs about the causes of myomas, and asked patients to rate them on a five-point scale of likelihood. Retrospectively, statistical analysis was performed on their answers and sociodemographic data. Results: Data from 482 patients was included (return rate of 91.5%). The most frequent answers for possible causes were "inherited susceptibility for myomas" (67.3%), "reorganization in the body during a particular phase of life" (63.5%), "stress at work or home" (49.3%) and "an in-born tendency to react to emotional agitation with physical disorders" (41.8%). Significant differences were found for the factors of age, immigration background and self-rated knowledge about myomas. Conclusions: It is curious that two of the four most common explanations for myomas were stress and somatization, and were endorsed by nearly half of all patients. Physicians seeing women for myomas should consider that many such patients may have further hidden reasons for seeking medical care.